Planck Scale Effects in Astrophysics and Cosmology - Amelino-Camelia, Giovanni; Kowalski-Glikman, Jurek (Lecture Notes in Physics,, 2005)
This volume is composed of extensive and detailed notes from the lectures given at the 40th Karpacz Winter School. This school focussed on quantum gravity phenomenology with emphasis on its relation to observational astrophysics and cosmology. These notes have been carefully edited with the aim to give advanced students and young researchers a balanced and accessible introduction to an rather heavily mathematical subject.